Determination and Analysis of Solubility of HC-290 (Propane) in [hmim][Tf2N] - Shi, Wei; Shi, Jianrong; Wang, Xiaopo (Processes, 2025)
Seeking the alternative working pairs used in absorption refrigeration cycles is one of the main issues in refrigeration fields due to the drawbacks of traditional H2O/LiBr and NH3/H2O, such as corrosion, crystallization, and toxicity. The imidazolium-based ionic liquid [hmim][Tf2N] has emerged as a promising candidate as an absorbent used in absorption refrigeration systems. In addition, due to having a higher specific heat and higher latent heat of evaporation, hydrocarbons such as HC-290 have been considered as good alternative refrigerants in compression refrigeration cycles. In order to explore the possibility of using HC-290 in the absorption refrigeration cycle, the exact phase behavior of HC-290 with absorbents should be known. Therefore, in this work, the isochoric saturation method was used to determine the solubility of HC-290 in [hmim][Tf2N] over a temperature range of 283.15 K to 343.15 K. The experimental data were modeled using the non-random two-liquid (NRTL) activity coefficient model and the Krichevsky–Kasarnovsky (K-K) fugacity model. The average absolute relative deviations for the mole fraction of HC-290 in [hmim][Tf2N] between this work and calculated results from the models were 0.76% (NRTL) and 0.78% (K-K), and the corresponding maximum relative deviations were 3.39% and 3.24%. Based on the NRTL model, the Gibbs free energy, enthalpy change, and entropy change in the dissolution process of HC-290 in [hmim][Tf2N] were calculated and discussed. Furthermore, the Henry’s constants of various refrigerants in [hmim][Tf2N] were calculated at 313.15 K and 333.15 K, and the results were systematically compared.